Interval type-2 hesitant fuzzy set method for improving the service quality of domestic airlines in Turkey - Deveci, Muhammet; Özcan, Ender; John, Robert; Öner, Sultan Ceren (Elsevier, 2018)
This study investigates the level of service quality of domestic airlines in Turkey travelling between Istanbul and London and compares those airline companies according to a set of predetermined criteria. A practical multi-criteria decision making approach combining hesitant and interval type 2 fuzzy sets is adopted and proposed for assessing the service quality of airline companies. The main finding of this study is that passengers care for service prioritization and personalization for a better flight experience and important differences occur in the service quality among the airline companies. Hence, handling of customer complaints, flight problems and individual attention could provide better insights for improving the service quality.